Penggunaan media pop up book dalam pembelajaran pendidikan pancasila materi makna simbol sila pancasila pada siswa kelas 4 di Sekolah Dasar - Rizka Marliana; Sukarno Sukarno; Siti Wahyuningsih (Universitas Sebelas Maret, 2023)
Abstract. The purpose of this research is to describe and analyze the use of pop up book media in teaching Pancasila education about the meaning of Pancasila symbols in grade 4 students at SD N Banmati 02 in the 2022/2023 academic year. The form of this research is a type of analytical research with a qualitative approach. The subjects of this study were 17 students and teachers of Pancasila education in grade 4 of SD N Banmati 02 for the 2022/2023 academic year. Data collection techniques are carried out by observation, interviews, and documentation. Test the validity of the data using the triangulation method. The data analysis step uses the Creswell analysis technique. The conclusion of this study is that the use of Pop Up Book media in learning planning is already in the good category but there are still obstacles including not reaching all students, it can only be used for visual learning styles, its use must be careful, and the production costs are expensive. The results of learning the material for the meaning of the Pancasila precepts using Pop Up Book media consisted of a formative assessment of 76% getting a score of 82 and above, and a summative assessment of 75% getting a score of 83 and above so that the use of Pop Up Book media was successful.